Efficacy and safety of 88% phenol application versus cryotherapy in repigmentation of idiopathic guttate hypomelanosis: A comparative study - Rajegowda, Harish Muddanahalli; Kalegowda, Deepadarshan; Madegowda, Shashikumar Basavapura; Rangarajaiah, Ambika C (Journal of Pakistan Association of Dermatologists, 2020)
Background Idiopathic guttate hypomelanosis (IGH) is a common, acquired dermatosis characterized by multiple, round or oval, hypopigmented to depigmented macules. A variety of therapies with variable success are described, despite that, the treatment remains still unsatisfactory and therapeutic challenge for dermatologists. Objective The objective of this study is to compare the safety & efficacy of 88% phenol application & cryotherapy in repigmentation of IGH macules. Materials and Methods A total of 30 patients with more than 10 IGH macules were selected. For each enrolled patient 88% phenol was applied to 5 IGH macules and single cryotherapy for 3-5 seconds was applied for another 5 IGH macules once in a month till the repigmentation for maximum of 3 applications. Patients were assessed monthly for 3 months for the side effects and improvement in pigmentation. The degree of improvement in pigmentation was assessed using a grading system, <25%- no response (grade-1), 26-50% minimal (grade-2), 51-75% good (grade-3) and >75% excellent response (grade-4). Results A total of 25 patients completed the study. At the end of the treatment period, out of 125 macules treated with short contact cryotherapy 75(60%) macules showed excellent response & 20(16%) macules showed good response. In phenol group, out of 125 macules 37(29.6%) & 29(23.2%) macules showed excellent & good improvement in pigmentation respectively, with p-value<0.05. Side effects like persistent scabbing, ulceration were more common with 88% phenol application compared to cryotherapy. Conclusion Short contact cryotherapy of 3-5 seconds was found to be more efficacious and safe compared to therapeutic wounding with 88% phenol in inducing pigmentation of IGH macules.